A concise history of the Middle East - Goldschmidt, Arthur, 1938-; Boum, Aomar (Westview Press, 2016)
An introduction to the history of this turbulent region from the beginnings of Islam to the present day, this widely acclaimed text by Arthur Goldschmidt Jr. is distinguished by its clear style, broad scope, and balanced treatment. This book explores the evolution of Islamic institutions and culture, the influence of the West, the modernization efforts of Middle Eastern governments, the struggle of various peoples for political independence, the Arabs ;Israeli conflict, the reassertion of Islamic values and power, the issues surrounding the Palestinian Question, and the post-9/11 Middle East. The.